The European central bank: a full-fledged scheme or just a “fledgeling”? - SARCINELLI, M. (PSL Quarterly Review, 2013)
This article attempts to answer the questions posed by many Europeans: ‘Is the proposition for a European Central Bank workable or not?’ In an attempt to provide an answer to such a complex question, the history associated with the idea of such an organisation is outlined as well as an exposition of its probable objectives and possible functions. JEL: E58